Multiyear Pavement-Rehabilitation Planning Enabled by Geographic Information System: Network Analyses Linked to Projects - Tsai, Yichang (James); Gao, Bo; Lai, James (Transportation research record, 2004)
A pavement-rehabilitation planning system enabled by a geographical information system (GIS) is described; it can perform multiyear projectlinked network pavement-rehabilitation analyses subject to funding availability, minimum performance requirements, and other constraints. The system first uses information on the current and historical project-level pavement-condition evaluation stored in the central database to forecast project performance ratings and distresses. It then determines appropriate rehabilitation methods and costs and, finally, calculates life-cycle costeffectiveness ratios for all projects in the pavement network. With this information, the program performs analyses to determine multiyear minimum funding required to meet prescribed pavement-performance requirements and constraints and to determine optimum pavementrehabilitation plans subject to funding availability and other requirements, such as balancing funding distribution or future pavement performance among state congressional districts or Georgia Department of Transportation (GDOT) districts. The system uses dynamic segmentation to create GIS maps, links them with the central database and network analysis results, and thus allows users to make changes to the rehabilitation plans directly on the GIS maps and have the changes reflected automatically in the database. Several examples using the actual data on historical pavement condition evaluations from GDOT are presented to illustrate the capabilities of the system.